The Influence of Professional Skepticism, Competence, Independence, Integrity and Moral Reasoning on Auditors Ability to Detect Fraud (An Empirical Study on Auditors of The Audit Board of The Republic of Indonesia (BPK-RI) Representative Office in Central Java Province) - Bate'e, Herlin Permata Hati Niaslin; Daeli, Dian Christitah Misionis; Wiliandika, Hapid (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
Fraud remains a persistent issue in both the public and private sectors, often causing significant financial and reputational damage. In the public sector, particularly in Indonesia, government auditors play a crucial role in detecting and preventing fraudulent practices. However, the effectiveness of auditors in identifying fraud depends on multiple personal and professional attributes. This study aims to examine the influence of professional skepticism, competence, independence, integrity, and moral reasoning on auditors’ ability to detect fraud at the Audit Board of the Republic of Indonesia (BPK-RI) Representative Office in Central Java Province. Using a quantitative research approach, data were collected through structured questionnaires distributed to 100 auditors selected using purposive sampling, requiring a minimum of three years of professional experience. The data were analyzed using multiple linear regression to test the relationships between the variables. The results reveal that independence and integrity significantly and positively affect auditors’ ability to detect fraud. However, professional skepticism, competence, and moral reasoning do not show a significant influence. These findings highlight the importance of maintaining auditors’ independence and ethical integrity as essential attributes for effective fraud detection, while also suggesting that technical competence and moral cognition alone may not suffice without adequate institutional and contextual support. The study contributes to the development of audit quality frameworks and provides practical implications for audit institutions aiming to strengthen fraud detection capacity.